Physical Punishment at School in Three Educational Systems in Pakistan - Nazia Nazar; Karin Osterman; Kaj Bjorkqvist (Universitas Ahmad Dahlan, 2019)
A questionnaire was completed by 1,100 students (550 girls, mean age 13.3 years, SD 1.0; 550 boys, mean age 14.1, SD 1.0) from three types of schools in Pakistan; Urdu medium, Elite English medium, and Madrassa. It included scales measuring frequency of victimisation from physical punishment by a teacher, physical injuries from being punished by a teacher, negative feelings after physical punishment by a teacher, reasons for being punished by a teacher, and acceptance of physical punishment at school. Boys had significantly more often been victimised from physical punishment than girls, with boys from Madrassas being more often victimised than all other groups. Students from English medium schools scored significantly lower on all scales than students from the other schools. Girls reported a significantly more accepting attitude towards physical punishment at Â school than boys. Students from Urdu medium schools scored significantly highest on acceptance of physical punishment at school, while boys from English mediums schools reported the significantly lowest level of acceptance. For both girls and boys, acceptance of physical punishment at school was positively correlated with the other scales.